Complex rearrangements of Y chromosome suggest RPS4Y1 as lymphedema candidate gene - Chen, Po-Fan; Kuan, Long-Ching; Kao, Chiu-Ching; Hsu, Hui-Kuo; Chen, Ming; Kuo, Tsung-Cheng; Kuo, Pao-Lin (Taiwanese journal of obstetrics & gynecology, 2022)
Cystic hygromas are frequently encountered in fetus with Turner syndrome (TS). Nevertheless, identification of genetic loci responsible for the cystic hygroma has been problematic. Here, we tried to elucidate the candidate gene for cystic hygroma through a rare case of complex Y chromosomal rearrangements involving duplication of partial Yq and monosomy of partial Yp. A 30-year-old woman, gravida 1 para 0, was diagnosed with fetal cystic hygroma at 12 weeks of gestation. The genetic analysis of the product of conception revealed complex rearrangement of Y chromosome: microdeletion in Yp11.2p11.31 and microduplicatin in Yq11.223q11.23. The deleted region spans about 6.25 Mb and includes 76 genes, including SRY. The duplicated region spans about 4.76 Mb and includes 145 genes. From this rare case with non-mosaic complex Y-chromosome rearrangements, we could narrow down Turner stigmata critical region to Yp11.2～p11.3. We also propose RPS4Y1 as lymphedema candidate gene.